Stefanie von Schnurbein, Norse Revival: Transformations of Germanic Paganism (Leiden: Brill, 2016), 418 pp., $140 (cloth), $25 (paper), Open Access (ebook). - Calico, Jefferson F. (Pomegranate, 2018)
Stefanie von Schnurbein, Norse Revival: Transformations of Germanic Paganism (Leiden: Brill, 2016), 418 pp., $140 (cloth), $25 (paper), Open Access (ebook).